Are natural resources a blessing or a curse for economic development? The importance of energy innovations. (August 2021) - Wang, Rong; Tan, Junlan; Yao, Shuangliang
Abstract: Based on China's provincial panel data from 2007 to 2019, this paper proposes the importance of energy innovation, uses the system GMM model to verify the impact of energy innovation on the resource curse effect, and supplements and improves the existing research. This study made the following findings: (1) The "resource curse" hypothesis exists in China. (2) Without considering other factors, natural resources and economic development are positively correlated, with a coefficient of 0.1872. (3) When the technology level variable is added, the coefficient of the natural resource variable drops to −0.1403. Due to the crowding-out effect, natural resources hinder economic development. (4) When the human capital variable is added, the natural resource coefficient is −0.2492. The "resource curse" is realized by crowding out the total amount of human capital accumulation. (5) When the material capital input variable is added, the coefficient of the natural resource variable is −0.163, but the absolute value drops significantly, indicating that the "resource curse" effect is alleviated. (6) When the energy innovation variable is added, the coefficient is 0.1401, and the coefficient of the natural resource variable is −0.1022, while the absolute value drops significantly, indicating that energy innovation largely alleviates the "resource curse" effect. Highlights: We use SYS-GMM models for empirical testing. We explore natural resources are a blessing or a curse. We offer suggestions for circumventing resource curses. We verify the importance of energy innovations.